2000
DOI: 10.1081/jdi-100100873
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Thromboelastography (Teg) and Filter Life During Continuous Veno-Venous Hemofiltration

Abstract: Anticoagulants are commonly used to prolong circuit life during continuous hemofiltration. However, a clear correlation between routinely performed blood coagulability tests and circuit life has not been demonstrated. This lack of correlation may derive from the limited ability of such tests to describe the likelihood of in vivo clotting. We hypothesized that thromboelastography (TEG), which derives its variables from a closer reproduction of in vivo coagulation, would significantly correlate with filter life.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(21 reference statements)
1
2
0
1
Order By: Relevance
“…We also found that heparin dose was an independent variable but that APTT and PT-INR were not, at least for normal or nearly normal values. These results are also consistent with previous studies [15, 17]and APTT has previously been shown to correlate poorly with serum heparin concentration [18]. Although frequent APTT measurements are often recommended for the monitoring or adjustment of heparin dosage to improve the efficacy of heparin-based filter anticoagulation [19], our findings do not support this recommendation.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…We also found that heparin dose was an independent variable but that APTT and PT-INR were not, at least for normal or nearly normal values. These results are also consistent with previous studies [15, 17]and APTT has previously been shown to correlate poorly with serum heparin concentration [18]. Although frequent APTT measurements are often recommended for the monitoring or adjustment of heparin dosage to improve the efficacy of heparin-based filter anticoagulation [19], our findings do not support this recommendation.…”
Section: Discussionsupporting
confidence: 45%
“…However, the observational period was relatively short (totally 19 months) and there were no other practice changes in the conduct of CVVH. Moreover, we observed more than 300 filters, which is more than any other published studies of filter life [8, 9, 10, 15, 17, 20, 21]. Thirdly, we did not measure small solute control (e.g.…”
Section: Discussionmentioning
confidence: 91%
“…Heparin protocols that account for heparin sensitivity in the previous circuit, as proposed by Ostermann, are one solution . There has also been interest in using thromboelastograms (TEG) instead of APTT; however, a prospective study found that TEG parameters did not predict circuit survival . Heparin potentiates the anticoagulant activity of AT‐III, the levels of which are reduced in the critically ill (particularly in sepsis).…”
Section: Discussionmentioning
confidence: 99%
“…Рутинный метод оценки тромбоцитов (например, количество тромбоцитов) не дает никакой информации об их функциональной активности. У критически больных пациентов наблюдаются различные уровни активации или дисфункции тромбоцитов, что также может повлиять на срок службы фильтра [5]. Поэтому, на наш взгляд, перспективным инструментом оценки баланса про/антикоагулянтов до и во время процедуры экстракорпоральной гемокоррекции может стать тромбоэластография.…”
Section: Discussionunclassified